2018
DOI: 10.2478/congeo-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of future changes in trends and scaling exponents in extreme short-term rainfall at selected stations in Slovakia

Abstract: This paper analyses projected changes in short-term rainfall events during the warm season (April – October) in an ensemble of 30 regional climate model (RCM) simulations. The analysis of trend changes and changes in scaling exponents was done for the Hurbanovo, Bratislava, Oravská Lesná, and Myjava stations in Slovakia. The characteristics of maximum rainfall events were analysed for two scenario periods, one past and one future (1960–2000 and 2070–2100) and compared to the characteristics of the actual obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Higher erosion rates could be attributed to changes in climate, as while overall precipitation have remained the same, extreme rainfall events occur more frequently in this region (Kohnová et al, 2018;Repel et al, 2020). The issue of climate change and its effect on vineyard erosion has been raised in many previous studies (Biddoccu et al, 2015;Eccel et al, 2016;Martı ́nez-Casasnovas et al, 2002;Serpa et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher erosion rates could be attributed to changes in climate, as while overall precipitation have remained the same, extreme rainfall events occur more frequently in this region (Kohnová et al, 2018;Repel et al, 2020). The issue of climate change and its effect on vineyard erosion has been raised in many previous studies (Biddoccu et al, 2015;Eccel et al, 2016;Martı ́nez-Casasnovas et al, 2002;Serpa et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…To evaluate the accuracy, we also established control measurements on a plot located on a flat area. Over the last decade, the intensity of rainfall‐driven erosion events has increased (Kohnová et al, 2018; Repel et al, 2020). Therefore, we replicated our measurements on experimental fields and the control plot to determine differences in erosion intensity and verify the accuracy of pole height method.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 Tests for monotonic trends in the parameter of location: the Mann-Kendall (MK) test, the test based on the Spearman's rho (S), and the Cox-Stuart (CS) test (Mann 1945, Kendall 1938, Cox and Stuart 1955. The MK test was used in a huge number of studies, examples of which are Hirsch et al (1982), Młyński et al (2019), Nowak et al (2019), Jeneiova et al (2014, Kohnová et al (2018), Meresa et al (2017). The examples for the CS test in hydrology are Fatichi et al (2009), Sen and Niedzielski (2010), Kosek (2011), Rutkowska (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Change in rainfall patterns (amount, intensity, and frequency) and other forms of precipitation is one of the most critical factors determining the overall impact of climate change on different regions (Food and Agriculture Organization of the United Nations [FAO], 2015; World Meteorological Organization [WMO], 2020). Evidence has shown that wet regions are likely to get wetter (Kumar et al, 2013), but details on how much wetter, and the impacts of this on a local scale, are more difficult to ascertain (Kohnová et al, 2018). Less than 10% of the Cerrado region is protected (Françoso et al, 2015); because of agribusiness, approximately half of the area has been converted into crops and pasturelands (Colli et al, 2020).…”
Section: Implications To the Cerrado Deforestation And Climate Change...mentioning
confidence: 99%